The Effect of Financial Literacy and Risk Perception on Financial Behavior Management in the Use of Peer To Peer (P2P) Lending Shopee Paylater on IIB Darmajaya Students - Faulina, Lavenia; Ramaputra, Muhammad Galih (Proceeding International Conference on Information Technology and Business, 2023)
The purpose of this study was to determine and analyze how much influence financial literacy and risk perception have on financial behavior management in the use of P2P Lending Shopee Paylater on IIB Darmajaya students. Researchers hypothesize that Financial Behavior Management in the use of P2P Lending for IIB Darmajaya students is caused by knowledge of Financial Literacy and Risk Perceptions where Financial Literacy and Risk perceptions affect the choice of using P2P Lending for IIB Darmajaya Students. This type of research is descriptive quantitative research, using a sample of 75 respondents who are Shopee Paylater users and are currently studying at IIB Darmajaya. The analytical tools used are SPSS software and Microsoft Excel. Keywords—financial literacy, risk perception, financial behavior management